On War - Clausewitz, Carl von, 1780-1831 (Book collections on Project MUSE., 2011)
The seemingly endless wars in Iraq and Afghanistan have renewed the age-old debate over what constitutes military victory. Will the withdrawal of troops from Iraq and Afghanistan be seen as a sign of victory or defeat? Although the nature of warfare has changed dramatically since Clausewitz'sOn War was first written, this selection from his classic work remains an invaluable source of insight for understanding what it means to achieve victory in war and how to recognize defeat. Princeton Shorts are brief selections excerpted from influential Princeton University Press publications produced e.